Dual-Band Aperture-Shared Fabry-Perot Cavity-Integrated Patch Antenna for Millimeter-Wave/Sub-6 GHz Communication Applications - Zhu, Jianfeng; Yang, Yang; Liao, Shaowei; Li, Shufang; Xue, Quan (IEEE antennas and wireless propagation letters, 2022)
This letter presents a dual-band antenna with a large frequency ratio of 11.7 (2.4 GHz/28 GHz) by integrating an mm-wave Fabry-Perot cavity (FPC) antenna into a sub-6 GHz patch antenna. The patch with periodic slots functions as both the 2.4 GHz radiator and the partially reflective surface (PRS) of the 28 GHz FPC antenna. By properly tuning the length of the periodic slot, the PRS's reflection can be easily adjusted. As the periodic slot's length and width operating at 28 GHz are much smaller than the wavelength at 2.4 GHz, periodic slot operating at 28 GHz have little impact on the radiation of the patch. Furthermore, because of the Fabry-Perot resonance, the antenna can have a peak gain reaching 15 dBi at 28 GHz band with an easy feeding structure. For demonstration, a prototype is fabricated and experimentally verified. Note that the frequency ratio is not limited to the proposed design (11.7 for demonstration). It can be easily adjusted based on the same principle.